A PROVEN AND RELIABLE STRATEGIC PARTNER OF UZBEKISTAN - Otabek Uktamjon ugli Rustamov (Journals Park Publishing, 2023)
In this article has been analyzed of interstate agreement on economic cooperation between the Republic of Uzbekistan and the Republic of Korea also in order to establish and develop the automobile industry in Uzbekistan by the helping primary sources.
Keywords: Republic of Uzbekistan, Republic of Korea, strategic partner, automobile industry, agreement, economic cooperation.